2020
DOI: 10.1177/0014402920926461
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Care and Education Settings on the Kindergarten Outcomes of Doubly Vulnerable Children

Abstract: Program administrators and policy makers have placed a priority on expanding access to inclusive, center-based early care and education (ECE) for low-income children with special needs, a “doubly vulnerable” population characterized by academic and social-emotional achievement gaps at kindergarten entry. Yet, no research has documented the effects of center-based settings on doubly vulnerable children’s early development, either relative to other ECE settings (e.g., home-based care) or relative to each other (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Finally, the study sample did not include children with disabilities and only included children from disadvantaged families; thus, findings should be generalized with caution. Although our findings regarding the main effects of pre-K are likely to replicate for children in universal programs and for children with disabilities, it is likely that the magnitude of benefits would vary (e.g., Schochet et al, 2020). Thus, continued work is needed to understand the persistence of these benefits across programs of different types and children from different backgrounds.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, the study sample did not include children with disabilities and only included children from disadvantaged families; thus, findings should be generalized with caution. Although our findings regarding the main effects of pre-K are likely to replicate for children in universal programs and for children with disabilities, it is likely that the magnitude of benefits would vary (e.g., Schochet et al, 2020). Thus, continued work is needed to understand the persistence of these benefits across programs of different types and children from different backgrounds.…”
Section: Discussionmentioning
confidence: 85%
“…Second, HS programs are required to provide all necessary modifications to the environment, instructional formats, and individualized accommodations to support the full participation of all children with disabilities (HSPPS, §1302.61). Schochet et al (2020) compared the effectiveness of HS and pre-k specifically when serving children with disabilities. Consistent with the broad literature comparing the effects of HS and state pre-k, they found that the effects of HS and pre-k did not differ across cognitive outcomes, but that HS was associated with higher approaches to learning and prosocial skills.…”
Section: Programming Emphasis On Children With Disabilitiesmentioning
confidence: 99%
“…Unmitigated effects of trauma have a lasting impact on students and can affect academic achievement and social emotional growth (Bell et al, 2013). School age students are in a developmentally vulnerable state (Schochet et al, 2020) and are developing executive functioning, which includes inhibitory control, cognitive flexibility, and a working memory; decreased executive functioning (Barr, 2019) leads to lower academic achievement and is linked to a higher dropout rate than their non-affected peers (Bell et al, 2013). Trauma's lasting impact on the brain can impede the development of executive function and lend towards low achievement and decreased self-regulation.…”
Section: Context and Backgroundmentioning
confidence: 99%
“…Teacher efficacy is a factor in students' willingness to be vulnerable (Delale-O'Connor et al, 2017;Wang et al, 2017). Vulnerability includes engaging in a deep dive in curriculum through a social justice lens (Schochet et al, 2020). Harvey et al (2016) notes, "Bandura (1997 defined self-efficacy as the belief in one's abilty to successfully produce desired effects through one's actions, which includes controlling aspects of one's environment" (p. 511).…”
Section: Teacher Self -Efficacy: Educating the Educatormentioning
confidence: 99%